(untitled) (Research, Society and Development, 2025)
This study aimed to investigate the medicinal plants used by the Rio do Sul quilombola community, located in the municipality of Nova Viçosa, Bahia. The “snowball” sampling technique was used to select participants, along with semi-structured interviews, sample collection, and photographic documentation of the plants. Fifteen interviews were conducted, identifying 97 medicinal plants. Most participants were women (86.7%), ranging from 47 to 93 years old. To assess the importance of the species, the main use agreement index (CUP) was applied, along with the correction factor (FC), using the corrected use agreement index (CUPc) for greater accuracy in the results. The data showed that leaves were the most frequently used plant part, representing 68% of citations. The most common preparation method was tea, cited by 77.3% of participants, followed by use in baths, mentioned by 35.1%. An analysis revealed that 99% of the identified plants were used for medicinal purposes, while 7.2% were used in spiritual practices and 4.1% were employed in food. The species with the highest corrected use agreement indices were: alfavaca (Ocimum gratissimum), with a CUPc of 75.0%; algodoeiro (Gossypium hirsutum), with 80%; hortelã-miúdo (Mentha x villosa) and erva-cidreira (Lipia alba), both with 77.8%; capim-limão (Cymbopogon citratus), with 85.7%; aroeira (Schinus terebinthifolius) and coentro-maranhão (Eryngium foetidum), both with 75%; as well as cajueiro (Anacardium occidentale) and tansagem (Plantago major), both with 83.3%. These findings highlight the importance of preserving traditional knowledge passed down through generations in the quilombola community.